A carbon nanotube non-volatile memory device using a photoresist gate dielectric. (November 2017) - Sun, Yun; Wang, Bing-Wei; Hou, Peng-Xiang; Liu, Chang; Fang, Lin-Lin; Tan, Jun; Sun, Dong-Ming; Cheng, Hui-Ming
Abstract: Carbon nanotube (CNT) thin films have attracted great attention for their use in flexible electronics, including thin-film transistors (TFTs) and memory devices, due to their excellent optical, electrical and mechanical properties. The flexibility of current CNT TFTs is usually limited by the use of rigid inorganic oxide insulators. Gate dielectrics made of polymers are promising candidates that give the device the desired flexibility. Here, we present a simple and effective method to format a patterned gate insulator using photoresist polymers to fabricate high-performance and good-flexibility CNT TFTs. The contact windows in gate insulators can be easily formatted for electrical interconnections in TFTs and integrated circuits, which will much simplify the fabrication processes. The fabricated CNT TFTs with a 1000-nm-thick photoresist insulator exhibited an on-off current ratio of 10 6, a mobility of 45 cm 2  V −1  s −1, a low operation voltage of less than 5 V, and a gate leakage current lower than 10 −11  A. A 5000-cycle bend test showed negligible changes to the mobility and on/off current ratio, demonstrating the good flexibility of the devices. A non-volatile memory device was demonstrated, showing the potential use of these flexible CNT-based electronics. Graphical abstract: A cured photoresist layer is qualified to be not only the gate dielectric in CNT TFTs, but also the passivation for a non-volatile memory device with good electrical performance.